Incumplimiento de los fines extrafiscales del IEPS a plaguicidas en México (Sección Abierta) - Gutiérrez Jiménez, Itzel (2026)
Non-tax purposes of taxes pretend to cause behaviors on contributors. One way to analyze its functioning is examining its collection trough time, because it is assumed that if the amount of collection decreases is because of the effectivity of the non-tax purpose. In Mexico there is a tax for sales of pesticides, which is regulated in Special Tax on Production and Services —named in Mexico as “Impuesto Especial sobre Produccion y Servicios” (IEPS)—, and its non-tax purpose es to decrease the consumption of those products. This paper analyses if during 2014 to 2023 that objective has been achieved, therefore that could be seen as a decrease in using, producing and selling pesticides, and in a lack of collection of this tax. Results show that, contrary to expectations, indicators increased during the period analyzed, therefore considering this analysis non-tax purpose has not been achieved. Absence of an official evaluation does not allow a technical discussion to modify this tax to achieve its objectives.